2018
DOI: 10.12659/msm.907073
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Inlet Parameters for Degenerative Cervical Spondylolisthesis Imaging Measurement

Abstract: BackgroundThe aim of this study was to explore the diagnostic value of sagittal measurement of thoracic inlet parameters for degenerative cervical spondylolisthesis (DCS).Material/MethodsWe initially included 65 patients with DCS and the same number of health people as the control group by using cervical radiograph evaluations. We analyzed the x-ray and computer tomographic (CT) data in prone and standing position at the same time. Measurement of cervical sagittal parameters was carried out in a standardized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Pan et al 121 (2017) reported similar changes of thoracic inlet alignment after the correction of posttuberculosis cervical kyphosis. Wang et al 122 (2018) presented higher T1S and TIA in cervical spondylolisthesis group than nonspondylolisthesis group but the NT was unchanged. Song et al 123 (2020) reported stable NT values and TIA after correction of kyphotic deformities in patients with Hirayama disease.…”
Section: "Where" To Go In the Future? 1 Thoracic Inlet Alignment Stumentioning
confidence: 97%
“…Pan et al 121 (2017) reported similar changes of thoracic inlet alignment after the correction of posttuberculosis cervical kyphosis. Wang et al 122 (2018) presented higher T1S and TIA in cervical spondylolisthesis group than nonspondylolisthesis group but the NT was unchanged. Song et al 123 (2020) reported stable NT values and TIA after correction of kyphotic deformities in patients with Hirayama disease.…”
Section: "Where" To Go In the Future? 1 Thoracic Inlet Alignment Stumentioning
confidence: 97%
“…Recently, after the concepts of the thoracic inlet angle (simihttps://doi.org/10.3340/jkns.2021.0011 lar to pelvic incidence in the thoracolumbar spine) and T1 slope (T1s) had been established, another derived factor (T1s minus cervical lordosis [CL]) has also been viewed as an essential parameter 15,25,26) . Although the usefulness of the above radiological parameters has been proven in many previous reports, the accurate measurement of T1s is not usually easy for many patients, due to their short necks or obstruction of shoulder shading 22) .…”
Section: Introductionmentioning
confidence: 99%
“…Lee found no direct correlation between pelvic parameters and thoracic or cervical spine alignment [12]. Kim found no statistically significant correlations were found among cervical kyphosis and the global spine parameters [4].…”
Section: Discussionmentioning
confidence: 83%
“…Usually, we use the C2-C7 angle to represent cervical lordosis(CL), but the relationship between cervical degeneration and cervical lordosis has been controversial. Wang observed no significant difference in the C2-7 angle between the normal group and the degenerative cervical spondylolisthesis group [12]. Generally speaking, the presence of a kyphotic cervical alignment may indicate substantial deformity and be linked to poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 92%